Development of an efficient heterologous protein expression platform in Aspergillus niger through genetic modification of a glucoamylase hyperproducing industrial strain - Fufan Gou; Dandan Liu; Chaohui Gong; Kefen Wang; Xingji Wang; Yefu Chen; Qian Liu; Chaoguang Tian (Microbial Cell Factories)
Abstract Background Aspergillus niger is widely used in industrial enzyme production due to its strong secretion capacity and the status of generally recognized as safe (GRAS). However, heterologous protein expression in A. niger is frequently constrained by high levels of background endogenous protein secretion, limited access to native high transcription loci, and limitations in the efficiency of the secretory machinery. To address these limitations, this study genetically engineered a chassis strain based on an industrial glucoamylase-producing A. niger strain AnN1 for constructing the improved heterologous protein expression. Results In this study, by using CRISPR/Cas9-assisted marker recycling, we deleted 13 of the 20 copies of the heterologous glucoamylase TeGlaA gene and disrupted the major extracellular protease gene PepA, resulting in the low-background strain AnN2. Compared to the parental strain AnN1, AnN2 exhibited 61% less extracellular protein and significantly reduced glucoamylase activity, while retaining multiple transcriptionally active integration loci. Four diverse proteins were integrated into the high-expression loci originally occupied by the TeGlaA gene in the chassis AnN2. These recombinant protein included a homologous glucose oxidase (AnGoxM), a thermostable pectate lyase A (MtPlyA), a bacterial triose phosphate isomerase (TPI), and a medical protein Lingzhi-8 (LZ8). All target proteins were successfully expressed and secreted within 48–72 h, with yields ranging from 110.8 to 416.8 mg/L in 50 mL shake-flasks cultivation. The enzyme activities of AnGoxM, MtPlyA and TPI reached ~ 1276 − 1328 U/mL, ~ 1627. 43 − 2105.69 U/mL, and ~ 1751.02 to 1906.81 U/mg after 48 h, respectively. Additionally, Overexpression of Cvc2, a COPI vesicle trafficking component, further enhanced MtPlyA production by 18%, highlighting the benefit of combining transcriptional and secretory pathway engineering. Conclusions Our results demonstrated that the chassis AnN2 served as a robust, modular, and time-efficient platform for heterologous protein expression in A. niger. Through site-specific integration of target genes into native high-expression loci and strategic modulation of the secretory pathway, we successfully enabled the rapid production of functional enzymes and bioactive proteins from diverse origins. This dual-level optimization strategy, which integrates rational genomic engineering with targeted enhancement of the secretory pathway, enabled high-yield expression while minimizing background interference. Together, these findings offer a practical framework for constructing versatile fungal expression systems and highlight the potential of combining genetic and cellular engineering to improve recombinant protein production in filamentous fungi.